Gender performance and the hyper-feminized cowgirl: a CTDA analysis of the @wprarodeo Tik Tok - Esposito, Cassidy L., author; Arthur, Tori Omega, advisor; Abrams, Katie, committee member; Aronis, Carolin, committee member (Colorado State University. Libraries, 2023)
This study evaluates the Women's Professional Rodeo Association TikTok as a social media platform that uses video to represent rodeo culture and portrays the cowgirl identity. This representation is centered within a male-dominant sport that falls under the agriculture industry and is rooted in other agriculture practices and history. It is important to understand how this androcentric experience in professional rodeo functions on social media through the @wprarodeo TikTok because social media representation in different forms is used to construct and reconstruct culturally situated identities. Using CTDA (Critical Technocultural Discourse Analysis) this study found three cultural ideologies including: the cowgirl appearance, athletic performance, and women empowerment through collective identity, which are present on the @wprarodeo TikTok as a representation of female narratives in professional rodeo, which are bolstered through Tik Tok's affordances. Tik Tok in an increasingly integrated digital space with highly intuitive user-based content and interaction.
Keywords: rodeo; women in sports; Tik Tok; gender performance